2018
DOI: 10.1038/s41438-018-0034-1
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of TAC1 expression in Prunus species leads to pleiotropic shoot phenotypes

Abstract: Prunus persica (peach) trees carrying the “Pillar” or “Broomy” trait (br) have vertically oriented branches caused by loss-of-function mutations in a gene called TILLER ANGLE CONTROL 1 (TAC1). TAC1 encodes a protein in the IGT gene family that includes LAZY1 and DEEPER ROOTING 1 (DRO1), which regulate lateral branch and root orientations, respectively. Here we found that some of the native TAC1 alleles in the hexaploid plum species Prunus domestica, which has a naturally more upright stature, contained a varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 43 publications
2
51
0
Order By: Relevance
“…6E, Supplementary Data File D4). A similar enrichment was reported for tac1 (pillar) peaches 17 . Supporting the known connection between LAZY1 and auxin transport, and in accordance with the lazy1 mutant phenotype, t0 lazy1 transcriptomes (when compared to t0 Col) were enriched for DEGs associated with hormone metabolism, the cell wall, and photosynthesis, among other categories ( Fig.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…6E, Supplementary Data File D4). A similar enrichment was reported for tac1 (pillar) peaches 17 . Supporting the known connection between LAZY1 and auxin transport, and in accordance with the lazy1 mutant phenotype, t0 lazy1 transcriptomes (when compared to t0 Col) were enriched for DEGs associated with hormone metabolism, the cell wall, and photosynthesis, among other categories ( Fig.…”
Section: Resultssupporting
confidence: 84%
“…Ectopic LAZY1 expression causes an EAR-domain dependent curled leaf phenotype. We previously reported that overexpression of TAC1 in plum trees resulted in wider branch angles 17 . However, we also reported TAC1 overexpression only partially complemented the tac1 Arabidopsis mutant phenotype, and in 24-hour light or dark conditions TAC1 overexpression in Col had little effect on branch angle 3,18 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…TAC1 belongs to a small family of genes. All the genes in the family, characterized to date in several plant species, including trees (poplar and plum) control branch or lateral root angles ( Figure 1 ; Xu et al, 2017 ; Hollender et al, 2018 ). Depending on presence of a conserved domain, members of the family can increase ( TAC1 ) or decrease ( LAZY1 ) branch angles ( Figure 1 ; Dardick et al, 2013 ; Hollender and Dardick, 2015 ; Xu et al, 2017 ).…”
Section: Manipulation Of Crown Architecturementioning
confidence: 99%